Chocolatology : chocolate's fantastical lore, bittersweet history, & delicious (vegan) recipes - York, Angel; Wick, Darin (Microcosm Publishing, 2018)
"A vegan cookbook and overview of the history and science of chocolate, with full color photography and illustrations"--